ORGANIZATION OF NON-FORMAL ACTIVITIES AND LEISURE OUTSIDE SCHOOL: ANALYSIS OF STUDENTS’ ATTITUDE - Radzeviciene, Liuda; Miliūnienė, Lina; Aluzas, Rytis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Study present the research aimed to reveal the situation of non-formal students’ activity. The process of non-formal education tends characterized by creating more flexible learning spaces, developing more caring and less hierarchical relationships, and aiming to meet participants’ needs. According to the research, the results discussed in two aspects: a) non – formal education implemented out of comprehensive school and b) non – formal education implemented in the comprehensive school. Having compared the attendance of non – formal education activity at school and out of comprehensive school according to gender, the results have shown that girls’ and boys’ choice of activity types is similar; girls are more involved into non – formal activities organized out of comprehensive school. Reasons participating in the activities of non – formal education are primary associated with general psychological status, life goals, motives and interests of students.